Effect of Corona Plasma Radiation on the Contact Angle and Wettability of Bamboo Surface - Alfajrin, Achmad Chalid Afif; Muhlisin, Zaenul; Komariah, Rahma Nur; Putra, Bintang Ridzky Ranindra; Nazuwatussya'diyah, Nazuwatussya'diyah; Arzi, Yudha Hamdi; Mardhiyatna, Mardhiyatna; Sari, Rizki Yustisia (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Bamboo is a widely utilized non-timber forest product, often innovated into laminated boards, particle boards, and plywood. The outer bamboo surface (skin) possesses high compressive strength but exhibits hydrophobic properties, limiting its wettability toward liquids. Plasma corona technology, operating at atmospheric pressure and using surrounding gases at a relatively low cost, offers a promising solution to modify bamboo surfaces by increasing their surface energy. This study aimed to analyze the hydrophilic resistance and wettability of bamboo surfaces treated with plasma corona, measured through contact angle analysis. The direct drop method was employed by dripping water and phenol formaldehyde (PF) fluids onto bamboo surfaces treated with plasma corona. Contact angle measurements were performed using ImageJ drop analysis software. Results demonstrated that plasma corona treatment significantly reduced contact angle values, improving surface wettability. Untreated bamboo surfaces showed contact angles of 72.7° for water and 111.5° for PF fluids, indicating limited wettability. Post-treatment, the contact angles decreased to less than 30° for water and below 90° for PF, signifying enhanced wettability. However, the hydrophilic properties were found to be non-permanent, with contact angle values gradually increasing over 13 days of observation. Among the tested parameters, plasma corona treatment with a current strength of 75 mA for 5 minutes provided the most optimal wettability improvement for water and PF fluids. This study highlights the effectiveness of plasma corona in enhancing bamboo surface wettability, making it more suitable for applications requiring adhesive bonding or fluid spreading in industrial processes.